Potensi Pengembangan Peternakan Sapi Potong di Kecamatan Seputih Banyak Kabupaten Lampung Tengah - I M A Ploransia; N Irwani; A A Candra (PETERPAN (Jurnal Peternakan Terapan), 2022)
Cattle are one of the most popular types of livestock and are widely cultivated by breeders in Indonesia, especially beef cattle, which are meat-producing livestock that have high protein content and economic value. Beef cattle breeding business in Indonesia is traditional in nature, maintenance by breeders is generally a relatively small number and is a side business. Central Lampung Regency has the opportunity to develop beef cattle farms, especially in Seputih Banyak District. The population of beef cattle in Seputih Banyak District is one of the largest in Central Lampung Regency. The potential for abundant agricultural waste at harvest can be used as a source of feed ingredients. The method used for sampling was purposive sampling with 86 breeders as respondents. The variables observed in the study were: ownership status of beef cattle, breeders age, farmer education level, breeding experience, total ownership of beef cattle, main job of breeders, supporting beef cattle business including the type of cattle kept, housing and labor, feed, capita, equipment and marketing. Based on the results and discussion of beef cattle ownership status as much as 77% self-owned, breeders 47% age 40-50 years, education level 45% high school graduates, farming experience 51%, total livestock ownership 62% <5 cattle, main job breeders 70% as a farmer, 76% of Bali's cattle and 72% of marketing use Dutch services. It can be concluded that Seputih Banyak Subdistrict, Central Lampung Regency has the potential to be used as a beef cattle development area.